2004
DOI: 10.1111/j.1464-5491.2004.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Carotid haemodynamic parameters as risk factors for cerebral infarction in Type 2 diabetic patients

Abstract: The results of this cross-sectional study showed that the measurement of haemodynamic parameters was useful, together with IMT, in estimating the risk of previous cerebral infarction in Type 2 diabetic patients. The predictive value of these parameters in identifying the risk of future cerebral infarction must await the results of future prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
7
23
0
Order By: Relevance
“…It appears that, in addition to traditional cardiovascular risk factors, renal function is strongly associated with renal vascular resistance, whereas blood pressure variables seemed to be the strongest determinant of carotid RI. Considering that carotid hemodynamic alterations are risk factors for ischemic stroke, 14 our findings may be consistent with the well-established fact that hypertension is one of the most important risk factors for stroke. 23 The mechanism of the regional differences in risk factors for an increase in vascular resistances remains incompletely understood and requires further investigation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It appears that, in addition to traditional cardiovascular risk factors, renal function is strongly associated with renal vascular resistance, whereas blood pressure variables seemed to be the strongest determinant of carotid RI. Considering that carotid hemodynamic alterations are risk factors for ischemic stroke, 14 our findings may be consistent with the well-established fact that hypertension is one of the most important risk factors for stroke. 23 The mechanism of the regional differences in risk factors for an increase in vascular resistances remains incompletely understood and requires further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…[11][12][13] With respect to carotid hemodynamics, Frauchiger et al 19 reported that RI of the CCA and of the internal carotid artery (ICA) was associated with atherosclerotic risk scores. Nakatou et al 14 also reported that the RI and pulsatility index of the CCA correlated significantly with atherosclerosis risk scores and the presence of brain infarction. In our study, RI of the CCA was associated with the CCA's IMT, further suggesting that RI of the CCA could also be a marker of atherosclerosis, although such an association between RI and IMT was weakened after adjustment for established cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We determined that IMT increased but PI and RI decreased in hemodialysis patients. However, Frauchiger [25] and Nakatou [26] in their studies reported that PI and/or RI increased parallel to IMT. In contrast, we determined a weak but negative correlation between right IMT and right PI.…”
Section: Discussionmentioning
confidence: 93%
“…Frauchiger et al [25] reported that IMT measured in the internal carotid artery (ICA) was correlated with RI, and the assessment of RI should be combined along with the measurement of IMT as a marker of generalized atherosclerosis in patients with vascular risk factors or clinical findings of atherosclerosis. Nakatou et al [26] showed that the measurement of PI, together with IMT, was more significant with regard to the risk of atherosclerotic process in patients with type 2 diabetes and stroke. The carotid IMT of hemodialysis patients were increased in our study, as in previous studies [16].…”
Section: Discussionmentioning
confidence: 98%